2022
DOI: 10.3389/fpsyg.2021.789207
|View full text |Cite
|
Sign up to set email alerts
|

Reading Comprehension in Both Spanish and English as a Foreign Language by High School Spanish Students

Abstract: Several studies have highlighted that reading comprehension is determined by different linguistic skills: semantics, syntax, and morphology, in addition to one’s own competence in reading fluency (accuracy, speed, and prosody). On the other hand, according to the Linguistic Interdependence Hypothesis, linguistic skills developed in one’s own native language (L1) facilitate the development of these skills in a second one (L2). In this study, we wanted to explore the linguistic abilities that determine reading c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…For what concerns the results of foundational and upper-level language skills, on the one hand, a part of the results traced L1 and L2-English between-domains relations (see, Brevik & Hellekjaer, 2018;Cueva et al, 2022;Kahan-Horwitz & Saba, 2018;Pae, 2019;Van Gelderen et al, 2004, 2007. Results showed that EFL secondary school students' L1 foundational language skills, such as vocabulary, syntactic/ grammar knowledge play a significant role on L2-English reading comprehension.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For what concerns the results of foundational and upper-level language skills, on the one hand, a part of the results traced L1 and L2-English between-domains relations (see, Brevik & Hellekjaer, 2018;Cueva et al, 2022;Kahan-Horwitz & Saba, 2018;Pae, 2019;Van Gelderen et al, 2004, 2007. Results showed that EFL secondary school students' L1 foundational language skills, such as vocabulary, syntactic/ grammar knowledge play a significant role on L2-English reading comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…This review also extends our understanding by showing that L1 foundational language skills can be easily transferable across L1 and L2-English regardless of their family language distance. In fact, L1 foundational language skills play a significant role for L2-English reading comprehension not only when L1 and L2 are closely related in terms of family language (see, Van Gelderen et al, 2007), for example, L1-Dutch and L2-English use the same alphabetic system and have many other similarities, but even when L1 and L2 are scarcely related (see, Cueva et al, 2022) or not related (see, Pae, 2019). Most of the studies focused on the transition between lower and upper secondary school.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations